How Does Livestock Contribute to the Efficiency of the Oases’ Farming Systems? - Sraïri, Mohamed Taher; Mansour, Salah; Benidir, Mohamed; Bengoumi, Mohammed; Alary, Véronique (Jordan Journal of Agricultural Sciences, 2019)
Multiple constraints, such as increased demographic pressure and growing competition for limited water resources, are significantly affecting farming systems in the oases. The combination of these constraining factors impacts the efficiency of inputs’ uses and hampers the incomes from agricultural activities. Livestock has always been a component of the oasis farming systems, covering a wide range of functions: transportation, soil preservation, income generation through meat and milk, draft, and saving. Faced with the recent changes, this study aimed to characterize the roles and contribution of livestock on the overall performances of the oasis farming systems. To do so, twelve farms illustrating four types of livestock systems were selected. Within each farm, we calculated common agricultural efficiency indicators to assess the use efficiency of the most critical production factors in the oasis: land, labor, water, and capital. The results demonstrated that efficient oasis farming systems rely on the crops/livestock association. Thereby, while providing self-consumed food products, livestock intensified farming systems (D’man prolific sheep with off-farm feed resources and dairy cattle) allow an increase in crops’ yields and their incomes. This is particularly obvious for date palms’ incomes, which benefit from the surplus irrigation of the underlying lucerne. In parallel, in specific contexts of the oases where the intensification of agriculture is quite impossible (for instance within areas with scarce groundwater or saline water, or in farms with limited capital) livestock remains the main source of income, adding value to the vast pastoral areas and the by-products of crops (wastes of dates, wheat bran, and straw, etc.).